Pengaruh Emotional Quotient dan Spiritual Quotient Terhadap Employee Performance dengan Psychologycal Capital Sebagai Variabel Mediasi: Studi pada Frontliner Bank Woori Saudara Regional 2 Jawa Barat - Indah Purnama Sari; Neuneung Ratna Hayati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study is motivated by the need to improve frontliner performance in the banking sector amid service digitalization and increasing customer expectations. Bank Woori Saudara Regional 2 West Java faces performance challenges, particularly due to the dominance of frontliners with relatively short tenure. This study aims to examine the effect of Emotional Quotient (EQ) and Spiritual Quotient (SQ) on Employee Performance, with Psychological Capital (Psychological Capital) as a mediating variable. The theoretical framework is based on emotional intelligence, spiritual intelligence, employee performance, and Psychological Capital, which consists of self-efficacy, hope, optimism, and resilience. This research adopts a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to 92 frontliners of Bank Woori Saudara Regional 2 West Java and analyzed using Sobel tests. The results show that EQ has no significant effect on Employee Performance, while SQ has a significant positive effect. Psychological Capital is unable to mediate the effect of EQ on Employee Performance, whereas Psychological Capital can mediate the effect of SQ on Employee Performance. This study concludes that strengthening employees' internal psychological aspects, particularly through the development of Psychological Capital and spiritual values, is an important factor in improving banking frontliner performance.